Performance of sunflower (Helianthus annuus L.) hybrids to boron levels in sandy loam soils of Odisha: PERFORMANCE OF SUNFLOWER HYBRIDS TO BORON LEVELS IN SANDY LOAM SOILS OF ODISHA - ANITA MAHAPATRA; S S TELLA; KULASEKARAN RAMESH (Journal of Oilseeds Research, 2021)
Field experiment conducted to find out the effect of soil applied boron on the yield attributes, yield and economics ofsunflower (Helianthus annuus L.) at OUAT, Bhubaneswar revealed that boron @ 1.5 kg/ha recorded highest yield attributing characters such as head diameter (18.6 cm), total number of seeds/capitulam (830), seed (2.10 t/ha), stover (5.28 t/ha) and oil yield (743.6 kg/ha) over B applied @ 1kg/ha. Among the hybrids tested, the productivity was in the descending order of KBSH-44 < KBSH-53 <RSFH-1887 < LSFH-171. However, oil yield (764.9 kg/ha) was highest with KBSH-53 followed by RSFH-1887 (715.1 kg/ha). Among the hybrids, KBSH-44 recorded highest B:C ratio of 1.94 and lowest (1.67) was with LSFH-171. In case of boron levels, highest B: C ratio was recorded due to application of Boron @1.5 kg/ha.